FROM DIAGNOSIS TO TREATMENT: A SYSTEMATIC REVIEW AND META-ANALYSIS OF PHARMACOLOGICAL INTERVENTION OPTIMIZATION IN POLYCYSTIC OVARIAN SYNDROME - Dr Amber Shams; Dr. Muhammad Shahid; Dr. Maryam Shafqat; Dr Robina Zahoor (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
**Introduction** Polycystic ovarian syndrome (PCOS) remains the most prevalent endocrine disorder affecting women within reproductive age, constituting **6–20%** of the global population. Its pathophysiological features include **insulin resistance (IR), hyperandrogenism, and metabolic dysfunction**, which commonly lead to obesity, subfertility, and increased cardiovascular risks. The treatment approach is centered around managing obesity, focusing on metabolic and hormonal regulation. As an **insulin-sensitizing drug**, Metformin, alongside Orlistat, a **lipase inhibitor**, has been widely used to mitigate the risks of **weight gain, dyslipidemia, and reproductive dysfunctions** associated with PCOS. However, their relative efficacy remains **controversial** and requires validated assessment. This systematic review and meta-analysis aimed to assess the **reproductive, biochemical, and clinical parameters** Orlistat and Metformin are administered to PCOS patients by synthesizing evidence from **RCTs** and thereby advancing the field of precision medicine in gynecologic endocrinology. **Materials and Methods** A **systematic literature search** was conducted on **PubMed, Medline, Scopus, Embase, and The Cochrane Library** from January 2000 to December 2024 using the **PRISMA guidelines**. Only **RCTs comparing Orlistat and Metformin in patients with PCOS treated sequentially or in parallel arms** were included. A **random effects model** was used for the meta-analysis of **weight loss, ovulation rate, insulin sensitivity, lipid profile, and androgen activity. Heterogeneity was tested using Cochran’s Q test and I² statistics**. **Results** Orlistat was **statistically superior in weight loss (MD -3.92 kg, 95% CI -5.61, -2.23; p < 0.001)** and in **reducing serum testosterone levels**. On the other hand, Metformin showed **greater improvements in fasting insulin (MD -1.98 µU/mL, 95% CI -3.44, -0.52; p = 0.004)** and **enhanced glucose tolerance**. For ovulation rate, there was **no statistically significant difference between both arms**. **Conclusion** The conclusions reinforce the **distinct metabolic effects** of both drugs—**Orlistat has advantages for control of body weight and lipids, while Metformin remains the most effective treatment for insulin resistance and diabetes control**. In practice, a **combined therapeutic approach of Orlistat with Metformin** may achieve **optimal reproductive and metabolic outcomes**, warranting further investigation in **large prospective studies**.